Calcifying pseudoneoplasms of the neuraxis (CAPNON): The great tumor mimicker - Elena Greco, MD; Omar Elmandouh, MD; Amit Desai, MD; Alok Bhatt, MD; Prasanna Vibhute, MD; Amit Aggarwal, MD (Radiology Case Reports, 2022)
Calcifying pseudoneoplasms of the neuraxis (CAPNON) are very rare intracranial lesions with less than 50 cases reported in literature. These are non-neoplastic in etiology and despite having unique imaging characteristics, are often misdiagnosed as a neoplastic condition like meningioma, chordoma and gliomas. These do not have any predilection for any age, gender or intracranial location and can be seen in a wide range of age groups. Despite having an imaging overlap with neoplastic conditions, CAPNONs have classic histopathologic findings including chondromyxoid matrix, palisading spindle cells and calcific or ossific metaplasia. As more cases are being described in literature the imaging features are also being better defined. We discuss the clinical, imaging and histopathological findings of 2 cases of CAPNON mimicking posterior fossa meningioma and glial neoplasm.